Cyrkularne inscenizacje tożsamości. O jednoujęciowych filmach Shahrama Mokriego - Tomasz Poborca (Studia Filmoznawcze)
The goal of this article is to reopen the debate over the relationship between aesthetics and ethics, using Shahram Mokri’s innovative poetics as an example. The author employs structural, comparative, and ideological analysis methods to examine Iranian one-take films. He situates the director’s filmography within the broader context of Iranian cinema history and provides a detailed description of the narrative loop tactics employed by Mokri in his works. Then he interprets the original style using Gilbert Simondon’s ontological concept of individuation and Judith Butler’s queer theory. Thus, he combines a look at the periphery of film production with an examination of the marginal position of entities resisting discursive hegemony. The author argues that the epistemic dissonance that results from the confrontation of a long take’s apparent realism with mise en abyme narrative strategies and chronological aporicity has the potential to reflect the complex nature of identity lability without resorting to explicitly political or philosophical content.